FACTORS AFFECTING THE SUCCESS OF THE IMPLEMENTATION OF BLUE FLAG WELFARE PROGRAM POLICY IN BANGKOK - Chansamruean, Danai; Tawmit, Sornchai; Bodeerat, Chot (Journal of Social Science and Cultural, 2023)
The objective of this research is to 1) study the level of success in implementing the national flag policy in the area of Bangkok 2) investigate the factors influencing the success of implementing the national flag policy in the area of Bangkok, and 3) study the recommendations for implementing the national flag policy in the Bangkok metropolitan area. The sample group used in the research consists of business operators participating in the national flag policy program in the Bangkok metropolitan area, which is still in operation in the year 2021, totaling 353 people. Data was collected using a questionnaire with approximately 5 levels of data analysis using statistical methods, including frequency, percentage, mean, standard deviation, and structural equation modeling. Research findings are as follows: The success in implementing the national flag policy in the Bangkok metropolitan area is generally at a high level. Factors such as the characteristics of business operators, distribution channels, and the network of national flag business operators have a positive impact on the success of implementing the national flag policy in the Bangkok metropolitan area, statistically significant at the 0.05 level. Business operators of national flag stores should diversify distribution channels, create genuine data for store management, build networks with other operators, and comply with government regulations in implementing the policy.